A client-centered commentary on Lietaer and Gundrum's verbal response modes. (2nd October 2018) - Moon, Kathryn
ABSTRACT: Therapist verbal response rating systems are subjective and not universally applicable. Two systems that evolved in the course of studying Carl Rogers transcripts are compared in terms of method, approach (experiential or client-centered), and results. The desirability of interpreting Rogers' verbal responses from within his theory of therapy is discussed. Lietaer and Gundrum's applications of his rating system to Rogers' responses are reexamined from the perspective of a client-centered therapist. Rogers' transcripts do not provide objective evidence that his practice of therapy is experiential.